2018
DOI: 10.1007/s00204-018-2299-4
|View full text |Cite
|
Sign up to set email alerts
|

The mycotoxin alternariol suppresses lipopolysaccharide-induced inflammation in THP-1 derived macrophages targeting the NF-κB signalling pathway

Abstract: Alternariol (AOH) is a secondary metabolite formed by black mold of the genus Alternaria alternata. Due to limited hazard and occurrence data, AOH is still considered as an “emerging mycotoxin” and, as such, not monitored and regulated yet. Recent studies indicate immunosuppressive effects in vitro by altering the expression of CD molecules and proinflammatory cytokines, which are indispensable in mounting an innate immune response. However, the mode of action by which AOH exerts its immunosuppressive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 45 publications
2
62
1
Order By: Relevance
“…In more detail, the IL‐1β induced transcription of the proinflammatory cytokines IL‐8, IL‐6, and IL‐1β (Figure A) was inhibited after 5 h of incubation as well as the secretion of IL‐8 (Figure ) was reduced after both 5 and 20 h of AOH exposure. Similar effects were reported for RAW 264.7 macrophages, BEAS lung epithelial cells, and THP‐1 cells, where AOH reduced LPS induced immune responses . As underlying mechanism, an inhibition of the LPS induced NF‐κB signaling pathway was reported in THP‐1 macrophages .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In more detail, the IL‐1β induced transcription of the proinflammatory cytokines IL‐8, IL‐6, and IL‐1β (Figure A) was inhibited after 5 h of incubation as well as the secretion of IL‐8 (Figure ) was reduced after both 5 and 20 h of AOH exposure. Similar effects were reported for RAW 264.7 macrophages, BEAS lung epithelial cells, and THP‐1 cells, where AOH reduced LPS induced immune responses . As underlying mechanism, an inhibition of the LPS induced NF‐κB signaling pathway was reported in THP‐1 macrophages .…”
Section: Discussionsupporting
confidence: 79%
“…Without additional inflammatory stimulus, AOH displayed a tendency to induce IL‐8 transcription after long‐term incubation (20 h), albeit in a concentration‐independent manner (Figure ). These findings are only in part supported by previous research, as AOH was reported to leave IL‐8 secretion unaffected in human primary macrophages or rather slightly reduce its transcription in THP‐1‐derived macrophages . This discrepancy might arise from differences between cell models of different tissue origin.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations